The Role of Advanced Information Technology in Tourism (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The integration of advanced information technologies (IT) into the tourism industry has transformed how tourism products are created, marketed, and managed. Innovations within the industry are increasingly focused on developing new tourism offerings, implementing modern marketing strategies, and utilizing cutting-edge management techniques supported by IT. A practice-based approach, like the ten types of innovation framework designed by innovation expert Larry Keeley, provides a valuable structure for understanding these advancements. By carefully assessing each innovation type, leaders in tourism can evaluate available resources, consider external and internal factors, and determine the ultimate goal of their innovative efforts. Once the goal is clear, the appropriate technological tools can be selected to achieve it. IT, in this context, emerges as one of the most accessible and versatile resources. Keeley’s model emphasizes the need to consider three key aspects of any company's operations, each of which can be enhanced through innovative technologies.